Developing Workbook Science plus English to Improve Studentsâ€™ Mastery of Science Content in English - Diah Pamelasari, Stephani; Md Yunus, Melor; Fibriana, Fidia; Vita Amalia, Andin (International Journal of Engineering and Technology, 2018)
One of the challenges of teaching English for Science students in Indonesia is the training to comprehend science content in English. They need to have the skill to improve their science development knowledge by exploring it through latest information from scientific journals and text books. In fact, most of the students have limited English proficiency that results in the limited variety source of their literature references. Their pre-test result was not satisfactory by only reaching the average of 67. To overcome the problem, the workbook that integrated English skill and science content was developed to support the learning process. The design of research was Research and Development consisting of conducting need analysis, designing product, expert validation, revising product, trial in small scale level, and using the product in the learning process. The instrument to gather the data was the validation sheet for the expert containing indicators of valid criteria of workbook from the aspect of the material, language and media, the students' response questionnaire related to the use of workbook and science content in English test. The data were analyzed descriptively based on the data obtained from the research. The validation from the experts of language, material and media to produce a valid and feasible product showed that the workbook was feasible to be used as instructional material. The result showed that the expert of material, language and media gave the score of respectively 100, 92 and 92. The workbook also proved to be effective to improve the students' mastery of science content in English material with the average of 80. The workbook entitled Science plus English was designed to revise the previous instructional material and it has never been developed as instructional material. The novelty is the integration of English skill lesson and science content.Â Â